Pelatihan Pengolahan Data Menggunakan Software SPSS di Kantor Lurah Bungo Pasang Kec. Koto Tangah - Lovia, Lita; Rismen, Sefna; Ramadoni, Ramadoni (LPPM Universitas Bumigora, 2023)
Limitations of officers in analyzing data in district offices. Most of these problems are caused by the lack of knowledge and expertise of the apparatus and the limited number of computers. The data in the district office is not stored properly, and there is no data management and technology-assisted data presentation. Implementation method by providing training and mentoring. The training provided is in the form of basic skills in using SPSS in presenting district population data. Its activities are training and assistance in presenting and processing data using the SPSS program in the Bungo Pasang District. The implementation of the service conducted interviews and provided questionnaires to find out the extent of the training participants' understanding of the use of SPSS software. The service team explained the presentation of the data accurately and concisely. District employees are helped in understanding and processing data using this SPSS software. District officers find it helpful in their work with the applications taught.